2008
DOI: 10.1098/rstb.2007.2239
|View full text |Cite
|
Sign up to set email alerts
|

Acoel development supports a simple planula-like urbilaterian

Abstract: Molecular approaches to the study of development and evolution have had profound effects on our understanding of the nature of the evolutionary process. Developmental biologists became intoxicated with fanciful notions of reconstructing genetic pathways of morphogenesis while evolutionary biologists were sobered by the fallacy of reconstructing organismal relationships along increasing grades of morphological complexity. Increased taxon sampling and improvements in analytical techniques are providing a new app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(105 citation statements)
references
References 80 publications
3
102
0
Order By: Relevance
“…Our previous study also indicated a similar implication based on the finding that the segmentation stage of A. gambiae showed the highest similarity with the expression profiles of mid-embryonic (around gastrula to organogenesis) stages of four vertebrate species (mouse, chicken, X. laevis and zebrafish; Irie and Kuratani, 2011). These studies, together with attempts to identify conserved molecular modules (Gerstein, 2014), may provide a way to investigate what molecular and morphological features the urbilaterian ancestor possessed (Hejnol and Martindale, 2008), though the number of species studied so far is limited and further investigation with a broader range of animals is needed.…”
Section: Phylogenetic Units and The Hourglass Modelsupporting
confidence: 54%
“…Our previous study also indicated a similar implication based on the finding that the segmentation stage of A. gambiae showed the highest similarity with the expression profiles of mid-embryonic (around gastrula to organogenesis) stages of four vertebrate species (mouse, chicken, X. laevis and zebrafish; Irie and Kuratani, 2011). These studies, together with attempts to identify conserved molecular modules (Gerstein, 2014), may provide a way to investigate what molecular and morphological features the urbilaterian ancestor possessed (Hejnol and Martindale, 2008), though the number of species studied so far is limited and further investigation with a broader range of animals is needed.…”
Section: Phylogenetic Units and The Hourglass Modelsupporting
confidence: 54%
“…This resulted in the previous dismissal of Acoelomorpha. Instead, our results indicate that Acoelomorpha is a clade and forms the most relevant outgroup for comparisons between protostomes and deuterostomes, providing critical insight into the origin, evolution and development of metazoan organ systems (Hejnol & Martindale 2008b;Bourlat & Hejnol 2009). Acoelomorphs possess an orthogonal nervous system (consisting of multiple longitudinal dorsal and ventral cords) and an anterior ring-shaped centralization (absent in some species; Raikova et al 2001).…”
Section: Discussion (A) Acoelomorpha As Sister Group To Other Bilateriamentioning
confidence: 84%
“…It matters a lot how Urbilateria, the forefather of a bewildering array of bilaterian body plans, actually looked like. The scenarios that led to the emergence of the body plan of each bilaterian phylum are going to be radically different depending on whether Urbilateria was a simple flatworm-like animal (as proposed decades ago by Libbie Hyman in her planuloid-acoeloid theory, 1951, see Hejnol and Martindale, 2008, for a modernized version) or an annelidlike segmented worm with a number of fully differentiated organ systems (the "complex" Urbilateria theory, Balavoine and Adoutte, 2003). In the former case, body plan emergence in bilaterians has involved mostly evolutionary convergences, supposedly selected for by strong and sustained selective pressures in favour of more "efficient" anatomies adapted to active life styles.…”
Section: Introductionmentioning
confidence: 99%